AN ORGANISATIONAL-ECONOMIC MECHANISM FOR DEVELOPING MICE TOURISM THROUGH FAMILY ENTREPRENEURSHIP IN UZBEKISTAN - O. M. Pardaeva, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
Uzbekistan has established ambitious targets for its tourism sector, including attracting 15.8 million foreign visitors and generating USD 4 billion in tourism export revenues. Achieving these targets requires addressing a structurally significant challenge: the pronounced seasonality of tourist arrivals, which concentrates economic activity and employment in a narrow peak period while leaving substantial human and physical resources underutilised for the remainder of the year. Objective: This study investigates the potential of MICE tourism (Meetings, Incentives, Conferences, and Exhibitions) — pursued through family-based entrepreneurial ventures — as a strategic mechanism for extending the tourism season, expanding employment, and strengthening the competitiveness of Uzbekistan's tourism sector in international markets. Methods: The study draws on a review of national tourism statistics covering visitor arrival patterns from 2016 to 2024, an analytical synthesis of domestic and international scholarly literature on business and MICE tourism, and the development of an original organisational-economic mechanism for promoting family-based MICE tourism enterprises in Uzbekistan. Results: Seasonal analysis confirmed that visitor arrivals fall markedly from October to March, identifying a clear off-peak window during which demand-side diversification is most needed. Review of the literature established that MICE tourism — encompassing corporate meetings, incentive travel programmes, professional conferences, and trade exhibitions — is widely recognised as a season-independent form of travel uniquely suited to generating year-round demand. The paper presents a structured organisational-economic mechanism through which family enterprises can be systematically integrated into MICE tourism delivery, coordinated by government regulatory bodies and supported by targeted incentive frameworks. Discussion: MICE tourism represents a high-value, low-seasonality segment that aligns well with Uzbekistan's strategic objective of diversifying its tourism product and increasing its share of international business travel markets. Family-based operators, when properly organised and supported, are well positioned to serve the accommodation, catering, excursion, and logistical needs of MICE visitors. Conclusion: Developing a coherent organisational-economic framework for family entrepreneurship in MICE tourism is a viable and necessary pathway toward resolving Uzbekistan's tourism seasonality problem and creating stable, year-round employment in the sector.